Abrasive Jet Machining for Micro-hole Drilling on Glass and GFRP Composites. (2018) - Suresh, R.; Sohit Reddy, K.; Shapur, Karthik
Abstract: In the present research work, effects of process parameters on the machine characteristics of GFRP composite and Borosilicate glass have been carried out. The drilling characteristics that have been investigated are material removal rate (MRR) and taper angle of the hole. The four process parameters were considered for the study - stand of distance, pressure, abrasive particle size and time taken. The significant parameters were identified and their effect on the MRR and taper angle were studied. The obtained results reveal that MRR is most influenced by the abrasive particle size and stand of distance.